Reading for life-long health - Shulman, Kaiulani; Baicker, Karen; Mayes, Linda (Frontiers in Pediatrics, 2024)
There is a strong, positive relationship between childhood literacy and physical and mental health outcomes in adulthood. Through primary care-based literacy interventions, pediatricians reach children and their families long before they enter traditional education venues. In so doing, pediatricians play a key role in children's school readiness and in turn health outcomes.The current state of childhood literacy in United States defines an increasingly urgent platform for the healthcare profession generally, and pediatricians specifically, to embrace. Through reviewing the existing literature on the impact of childhood literacy on physical, mental, and social-emotional health outcomes, we hope to highlight the need for increased collaboration between the education and medical fields to further promote the literacy interventions in pediatric healthcare settings.